Mind your language: enhancing medical student learning during non-English language consultations - Haque, Enam; Naveenan, Thulasi; Shimwell, Genevieve; Farikullah, Jasmin; Lindley, Rachel; Marsden, Helen (Frontiers in Medicine, 2025)
General Practice provides an excellent opportunity for students to see patients with undifferentiated presentations and to acknowledge how General Practitioners (GPs) deal with medical complexity, uncertainty and psycho-social issues facing patients. It is essential that students have experience of diverse patient groups, using interpreters to help with language barriers. However, many practices have GPs that speak multiple languages, and patients appreciate the opportunity to speak their own language. The challenge for students is understanding what is happening when observing these consultations. The Community Team in a UK medical school was aware of the issues, through student evaluation data. To address this, they developed a protocol to support GP Clinical Placement Supervisors (CPS) to ensure the best clinical experience for their students, particularly in practices where consultations were not commonly delivered in English. This work developed into CPS training delivered locally and nationally at other medical schools in the UK. It also led to development of an experiential learning session, where students attended a practice with non-English consultations in the morning, and then reflected on the experience in the afternoon. It now forms a core part of the student curricular content in the Year 4 GP block. This paper highlights the journey to ensure that students can have meaningful learning, in environments where language may be a perceived barrier. It has enabled our students to appreciate the diversity and rich culture of our patients and take forward the learning gleamed from the complexities of non-English consultations.